2004
DOI: 10.1038/431525b
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic ERBB2 kinase mutations in tumours

Abstract: The protein-kinase family is the most frequently mutated gene family found in human cancer and faulty kinase enzymes are being investigated as promising targets for the design of antitumour therapies. We have sequenced the gene encoding the transmembrane protein tyrosine kinase ERBB2 (also known as HER2 or Neu) from 120 primary lung tumours and identified 4% that have mutations within the kinase domain; in the adenocarcinoma subtype of lung cancer, 10% of cases had mutations. ERBB2 inhibitors, which have so fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
502
4
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 712 publications
(536 citation statements)
references
References 7 publications
24
502
4
6
Order By: Relevance
“…Mig-6 is normally expressed in lung (data not shown) and plays a role in mechanical stress pulmonary ventilation (Makkinje et al, 2000). Also, MIG-6 is a negative regulator of receptor tyrosine kinase signaling from factors like EGF (Fiorentino et al, 2000) and HGF/SF (Figures 1 and 2; Pante et al, 2005), whose receptors have been shown to play important roles in lung malignancy (Zochbauer-Muller et al, 2002;Birchmeier et al, 2003;Ma et al, 2003Ma et al, , 2005Paez et al, 2004;Stephens et al, 2004). All this evidence supports MIG-6 as a tumor-suppressor gene.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Mig-6 is normally expressed in lung (data not shown) and plays a role in mechanical stress pulmonary ventilation (Makkinje et al, 2000). Also, MIG-6 is a negative regulator of receptor tyrosine kinase signaling from factors like EGF (Fiorentino et al, 2000) and HGF/SF (Figures 1 and 2; Pante et al, 2005), whose receptors have been shown to play important roles in lung malignancy (Zochbauer-Muller et al, 2002;Birchmeier et al, 2003;Ma et al, 2003Ma et al, , 2005Paez et al, 2004;Stephens et al, 2004). All this evidence supports MIG-6 as a tumor-suppressor gene.…”
Section: Discussionmentioning
confidence: 74%
“…The expression of MIG-6 is induced by EGF, whose signaling plays an important role in normal lung development (Miettinen et al, 1995(Miettinen et al, , 1997. Like many other tyrosine kinase receptors, EGF receptor signaling needs to be attenuated after activation; constitutive activation is deleterious to normal lung epithelial cells and can lead to carcinogenesis (Zochbauer-Muller et al, 2002;Paez et al, 2004;Stephens et al, 2004). MIG-6 interacts with the ErbB receptor family and negatively regulates EGF signaling (Fiorentino et al, 2000;Anastasi et al, 2003;Xu et al, 2005a), thereby providing through negative feedback a fine tuning of EGF signaling shortly after its activation.…”
Section: Discussionmentioning
confidence: 99%
“…36 The utility of the genes included in the WUCaMP assay has been well documented in prior clinical studies, and treatment decisions can be directly affected by the detection of certain mutations in the WUCaMP gene set. For example, there are certain mutations in the kinase domains of genes that predict response to specific targeted therapies: EGFR and ERBB2 mutations in nonesmall cell lung cancer, 37,38 JAK2 mutations in myeloproliferative disorders, 39 BRAF mutations in melanoma, 40 ALK mutations in neuroblastoma, 41 and KIT and PDGFRA mutations in gastrointestinal stromal tumors. 42 In contrast, other mutations predict resistance to therapy; for example, detection of codon 12 mutations in KRAS predicts resistance to treatment with EGFR tyrosine kinase inhibitors in lung cancer 43 and resistance to treatment with anti-EGFR monoclonal antibodies in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have searched for ERBB2 mutations in breast tumors and cell lines using a candidate mutation approach, sequencing of pooled amplicons, or sequencing of individual ERBB2 alleles from tumors with gene amplification. Stephens et al 24 None of these studies had specifically targeted the binding site of trastuzumab. Given the discovery of the crystal structure of ERBB2 receptor, illustrating the binding site with trastuzumab 11 and the mystery of trastuzumab resistance, we thought of specifically targeting the trastuzumab binding site, looking for possible mutation that could explain this resistance.…”
Section: Discussionmentioning
confidence: 99%